ANALISIS PERHITUNGAN HPP PAVING BLOCK DENGAN METODE PROCESS COSTING PADA CV SUMBER KARYA MADIUN - Putri, Fadya Astari; Devinda, Freza Natasha; Hartono, Halleina Rejeki Putri (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2025)
Every manufacturing company requires accurate cost information to support managerial decision-making, especially in determining the cost of goods manufactured. CV Sumber Karya Madiun is a micro, small, and medium enterprise (MSME) operating in the field of paving block manufacturing, characterized by a mass, continuous, and homogeneous production process. However, the company has not fully implemented a structured cost recording system. This study aims to analyze the calculation of the cost of goods manufactured using the process costing method. The research method used is descriptive quantitative, involving data collection through interviews, observations, and documentation at the company. Data analysis includes classifying costs into direct materials, direct labor, and factory overhead, then allocating these to three departments: Mixing, Molding, and Drying. The results show that the total production cost for February 2025 reached Rp743,471,375. The cost was distributed across three departments: Rp172,148,000 for the Mixing Department, Rp189,943,000 for the Molding Department, and Rp391,380,375 for the Drying Department. Each department’s cost was allocated according to its production function, and equivalent units were used in the drying department to calculate partially completed units and defective products. The implementation of process costing at CV Sumber Karya Madiun has the potential to enhance the accuracy of cost allocation, as well as support the establishment of more competitive selling prices and more effective future production cost planning.